Mobile device users' privacy security assurance behavior: A technology threat avoidance perspective. (10th July 2017) - Chen, Hao; Li, Wenli
Abstract : Purpose: Recently, the spread of malicious IT has been causing serious privacy threats to mobile device users, which hampers the efficient use of mobile devices for individual and business. To understand the privacy security assurance behavior of mobile device users, this study aims to develop a theoretical model based on technology threat avoidance theory (TTAT), to capture motivation factors in predicting mobile device user's voluntary adoption of security defensive software. Design/methodology/approach: A survey is conducted to validate the proposed research model. A total of 284 valid survey data are collected and partial least square (PLS)-based structural equation modeling is used to test the model. Findings: Results highlight that both privacy concern and coping appraisal have a significant impact on the intention to adopt the security defensive software. Meanwhile, privacy security awareness is a crucial determinant to stimulate mobile device user's threat and coping appraisal processes in the voluntary context. The results indicate that emotional-based coping appraisal of anticipated regret is also imperative to arouse personal intention to adopt the security tool. Practical implications: This result should be of interest to practitioners. Information security awareness training and education programs should be developed in a variety of forms to intensify personal security knowledge and skills. Besides, emotion-based warnings can be designed to arouse users' protection behavior. Originality/value: This paper embeds TTAT theory within the mobile security context. The authors extent TTAT by taking anticipated regret into consideration to capture emotional-based coping appraisal, and information security awareness is employed as the antecedent factor. The extent offers a useful starting point for the further empirical study of emotion elements in the information security context.